Health outcomes in spinal muscular atrophy type 1 following AVXS‐101 gene replacement therapy. Issue 2 (12th December 2018) - Al‐Zaidy, Samiah; Pickard, A. Simon; Kotha, Kavitha; Alfano, Lindsay N.; Lowes, Linda; Paul, Grace; Church, Kathleen; Lehman, Kelly; Sproule, Douglas M.; Dabbous, Omar; Maru, Benit; Berry, Katherine; et al.
Abstract: Background: Spinal Muscular Atrophy type 1 (SMA1) is a rare genetic neuromuscular disease where 75% of SMA1 patients die/require permanent‐ventilation by 13.6 months. This study assessed the health outcomes of SMA1 infants treated with AVXS‐101 gene replacement therapy. Methods: Twelve genetically confirmed SMA1 infants with homozygous deletions of the SMN1 gene and two SMN2 gene copies received a one‐time intravenous proposed therapeutic dose of AVXS‐101 in an open label study conducted between December 2014 and 2017. Patients were followed for 2‐years post‐treatment for outcomes including (1) pulmonary interventions; (2) nutritional interventions; (3) swallow function; (4) hospitalization rates; and (5) motor function. Results: All 12 patients completed the study. Seven infants did not require noninvasive ventilation (NIV) by study completion. Eleven patients had stable or improved swallow function, demonstrated by the ability to feed orally; 11 patients were able to speak. The mean proportion of time hospitalized was 4.4%; the mean unadjusted annualized hospitalization rate was 2.1 (range = 0, 7.6), with a mean length of stay/hospitalization of 6.7 (range = 3, 12.1) days. Eleven patients achieved full head control and sitting unassisted and two patients were walking independently. Conclusions: AVXS‐101 treatment in SMA1 was associated with reduced pulmonary and nutritional support requirements, improved motor function, and decreased hospitalization rate over the follow‐up period. This contrasts with the natural history of progressive respiratory failure and reduced survival. The reduced healthcare utilization could potentially alleviate patient and caregiver burden, suggesting an overall improved quality of life following gene replacement therapy. Trial registration: ClinicalTrials.gov number, NCT02122952.